Electromagnetic vibrational energy harvester with targeted frequency-tuning capability based on magnetic levitation - Chengbo Hu; Xinyi Wang; Zhifei Wang; Shudong Wang; Yuanyuan Liu; Yunjia Li (Nanotechnology and Precision Engineering)
This article presents a compact magnetic levitation energy harvester (MLEH) with tunable resonant frequency. Unlike many of the reported tunable harvesters with unknown tuning results, the proposed MLEH can be tuned toward designated resonant frequency values within its tuning range. The targeted tuning processes is realized by a nonlinear magnet repulsive force exerted on a Halbach magnet array, combined with a calibrated scaling system. At a sinusoidal acceleration of ±0.15 g, the maximum frequency tuning range of the proposed MLEH is 6.3 Hz (8.1–14.4 Hz), which is 77.8% of its resonant MLEH (8.1 Hz). At a frequency of 9.7 Hz, the output power is 462.1 μW and the calculated normalized power density is 496 μW cm−3 g−2.